THE EDUCATIONAL AND SOCIAL SIGNIFICANCE OF HISTORICAL MEMORY AND NATIONAL IDENTITY AWARENESS - Tursunova, D.A. (Oriental Journal of History, Politics and Law, 2026)
This article provides a comprehensive analysis of the theoretical and methodological foundations of historical memory and national identity, their socio-philosophical essence, and their educational significance. Historical memory is examined as a crucial phenomenon that preserves social experience and cultural heritage, while also serving as a key factor in the formation of national identity. The study highlights the role of national identity in the processes of socialization, moral development, and the formation of civic consciousness. It further explores the dialectical relationship between historical memory and national identity, as well as their transformation in the context of globalization. The findings indicate that historical memory plays a fundamental role in shaping historical consciousness, whereas national identity strengthens social belonging and value orientation. The integration of these concepts into the educational process is identified as an effective pedagogical mechanism for fostering the holistic development of individuals.